Scientific Explanations of Metalearning in Students - Marius-Costel Eși (Journal of Education, Society & Multiculturalism, 2025)
When discussing meta-learning in students, our analysis must undoubtedly focus on the main strategies for approaching such a process. In this regard, we consider meta-learning as a specific way of engaging with learning. Such an approach highlights the very concept of metacognition, which entails a comprehensive process of self-regulation in learning itself. Within this context, the aim of this paper is to examine the impact of meta-learning on students in an educational setting. Therefore, we seek to determine the extent to which such an analysis proves effective in the learning process.